2020
DOI: 10.1007/s42843-020-00017-y
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering and Resolving Social Conflicts Contributing to Chronic Pain: Emotional Awareness and Expression Therapy

Abstract: Chronic pain is pain experienced on most days for three months or more. It is one of the most frequent patient reported problems. It can be a primary or a secondary symptom. A number of psychological factors predict the development and impact of chronic pain. Adverse social experiences as well as stressful conflictual interpersonal interactions can precipitate and exacerbate chronic pain. Emotional awareness and expression therapy (EAET) is an approach to addressing interpersonal and emotional conflict with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Besides pain catastrophizing, factors such as stress, anger, poor communication skills, and limited assertiveness can affect pain intensity among patients with chronic conditions. For example, a study found stress, social conflicts, and non-assertive relationships as aggravating factors of chronic pain [ 8 ]. Studies into occupational therapy for chronic pain also emphasize that patients with limited problem solving, communication, and assertiveness skills may have problems in pain management [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides pain catastrophizing, factors such as stress, anger, poor communication skills, and limited assertiveness can affect pain intensity among patients with chronic conditions. For example, a study found stress, social conflicts, and non-assertive relationships as aggravating factors of chronic pain [ 8 ]. Studies into occupational therapy for chronic pain also emphasize that patients with limited problem solving, communication, and assertiveness skills may have problems in pain management [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…communication skills, assertiveness, stress management, lifestyle enhancement skills and physical activity. ( 19 ) Educational materials for topics were prepared as PowerPoint presentation slides in Shareable Content Object Reference Model (SCORM) format, then scenarios and audio explanations about educational materials were added to each slide. Accordingly, seven sets of educational materials were prepared in seven CDs for seven educational sessions.…”
Section: Methodsmentioning
confidence: 99%